The Making of Democratic Citizens: How Regime‐Specific Socialization Shapes Europeans' Expectations of Democracy. Issue 1 (4th December 2018) - Heyne, Lea
Abstract: When analysing support for democracy, researchers tend to assume that 'democracy' is a concept that travels across countries. This paper argues that democracy is not the same thing for every citizen, because collective and individual socialization experiences strongly shape the criteria citizens expect a democracy to fulfil. Based on the literature on varieties of democracy, I suppose that individual expectations of democracy are influenced by regime‐specific socialization, and depend on the democratic history, authoritarian legacies, and the prevalent democratic model. Due to socialization and democratic learning, individuals acquire democratic preferences and value those dimensions more which they experience in their own democracy. Using data from the European Social Survey (ESS) and the Democracy Barometer, I test how the national democratic context in 26 European democracies influences these individual democratic ideals. I find evidence for both socialization and participation effects of the democratic context on citizens' democratic expectations.